Dynamic alterations in decoy VEGF receptor-1 stability regulate angiogenesis - Joshua M. Boucher; Ryan P. Clark; Diana C. Chong; Kathryn M. Citrin; Lyndsay A. Wylie; Victoria L. Bautch (Nature Communications, 2017)
Membrane-bound mVEGFR1 is a decoy VEGF-A receptor that regulates VEGF-A signalling amplitude. Boucheret al. show that Rab27a-regulated palmitoylation of mVEGFR1 redirects the receptor from a stable, constitutively recycling mode to a degradative route that removes ligands from the system.